2008
DOI: 10.1002/bit.21909
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing agents enhance fungal degradation of polycyclic aromatic hydrocarbons and affect diversity of indigenous bacteria in soil

Abstract: The impact of several mobilizing agents (MAs) (i.e., soybean oil, Tween-20, Tween-80, olive-oil mill wastewaters, and randomly methylated beta-cyclodextrins) on the degradation performances of the white-rot fungi Irpex lacteus and Pleurotus ostreatus was comparatively assessed in a soil spiked with a mixture of seven polycyclic aromatic hydrocarbons (PAHs). Among the different MAs, soybean oil best supported the growth of both fungi that was twice that observed in soil in the absence of MAs. In addition, soybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 56 publications
5
31
1
Order By: Relevance
“…The effect was studied in detail with a model soil that was artificially contaminated with PAHs. In this case soybean oil and Tween 80 best supported the degradation activity of I. lacteus and their effect was remarkable toward phenanthrene, anthracene, fluoranthene, chrysene and benz[a]pyrene (Leonardi et al 2008) Bhatt et al (2000 tested the degradation of RBBR dye in an artificially contaminated soil (150 mg dye per kg dry soil) using I. lacteus, a bacterial consortium isolated from a soil industrially contaminated with dye effluents, and a coculture comprising both I. lacteus and this bacterial consortium. Both I. lacteus and the coculture removed RBBR gradually during a 49-d experiment to reach a removal of 76 and 78 %, respectively.…”
Section: Contaminated Soilmentioning
confidence: 86%
“…The effect was studied in detail with a model soil that was artificially contaminated with PAHs. In this case soybean oil and Tween 80 best supported the degradation activity of I. lacteus and their effect was remarkable toward phenanthrene, anthracene, fluoranthene, chrysene and benz[a]pyrene (Leonardi et al 2008) Bhatt et al (2000 tested the degradation of RBBR dye in an artificially contaminated soil (150 mg dye per kg dry soil) using I. lacteus, a bacterial consortium isolated from a soil industrially contaminated with dye effluents, and a coculture comprising both I. lacteus and this bacterial consortium. Both I. lacteus and the coculture removed RBBR gradually during a 49-d experiment to reach a removal of 76 and 78 %, respectively.…”
Section: Contaminated Soilmentioning
confidence: 86%
“…However, Leonardi et al [78] reported that depending on the fungi, the laccase activity in soybean amended soil can be enhanced or reduced (I. Lacteus and P. Ostreatus respectively).…”
Section: Enhanced Pah Degrading Enzyme Productionmentioning
confidence: 96%
“…For PAH degrading white-rot fungi, the use of vegetable oil could significantly serve as an extra carbon and energy source to support fungi growth, either in the soil system [78] or liquid cultures [79,80]. This is of particular significance since 5-ring and above PAHs are mainly degraded by fungi through their non-specific extracellular enzyme.…”
Section: Extra Carbon and Energy Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, on the design of reporter systems, the lux gene expression was used to evaluate the bioavailability of PHE. This is mainly because bacterial luminescence has two major advantages for detecting PAHs and other sparingly soluble compounds: a faster response time and higher shortterm sensitivities (Leonardi et al 2008). Both advantages allow a relatively small number of reporter molecules to produce a sufficient and strong signal.…”
Section: Resultsmentioning
confidence: 99%